(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Organizational citizenship behavior is among the most alluring behaviors in present day associations, albeit without any enforceable necessities. It is accepted that a few people, in light of what their identity is, would be bound to show such behaviors (Elanain, 2007). As it were, pre-demeanors of a worker like personality traits can be a wellspring of his presentation of OCB. Keeping it in see, the present paper means to recognize the relationship between these two develops based on examines led all through the world. The present examination includes a broad survey of the writing accessible on different database sources like Emerald, Taylor and Francis, Science Direct and so forth. Based on survey, ends and proposals for future specialists have been given.